Heavy metal speciation in sediment of the South China Sea off the Pahang coast, Malaysia during the pre- and post- North-east monsoon period - Shazili, N.A.M.; Ming, C.K.; Yunus, Kamaruzzaman (2012)
In a study to determine whether or not the Northeast Monsoon has a major effect on the distribution of metals in sediments, total Al, Cr, Fe, Mn, Ni, Pb and Zn were measured in twenty six surface sediment samples were collected from the South China Sea in the near-shore area off Pahang State of peninsular Malaysia during the pre- and post-Northeast monsoon periods. To gain a better understanding of the influence of chemical processes affecting metal distribution in sediments as a result of the monsoon, the distribution of the metals in chemical fractionations of the sediment were also determined. The mean concentrations of total metals studied were considered low compared to crustal value and regional studies. The metal distribution is related to input from a number of rivers entering the study area. All metals studied (Al, Cr, Fe, Mn, Ni, Pb and Zn) and their chemical fractions were mostly higher in concentrations in the coastal sediments off Kuantan port, in the northern sector of the study area. This is possibly due to the runoff of metal contaminants from land through the Kuantan River estuary area which was a highly built up area, with oil and gas industries, a port and urban areas. In the southern sector of the study area, the relatively high concentrations of metals may originate from run-off from the Rompin River estuary and also from large coastal aquaculture activities in the Nenasi area. The monsoon was clearly seen to have some effect on metal distribution within the chemical fractions, because the proportion of metals increased in the bio-available fraction in sediments collected after the North-east monsoon. After the NE monsoon, a large reduction in enrichment factor (EF) values were found for Pb and Zn in the sediment throughout the study area suggesting that these metals were diluted and/or redistributed within the sedimentary environment. It is thought that input of fresh clean sediment from monsoon run-off via Pahang, Kuantan, Bebar, Merchong and- Rompin rivers dilutes the metal contents in the Pahang coastal sediments. Alternatively or together with dilution, the sediments are redistributed and mixed resulting in overall dilution of metal concentrations. Metal fractionations patterns were significantly different between pre- and post- NE monsoon sediments, especially in exchangeable-Fe-Mn oxide, carbonate-Fe-Mn oxide and carbonate-residual fractions. This study shows that the Northeast Monsoon has the effect of redistributing the sediments as well as affecting the distribution of metals within the different chemical fractions of sediment.